Parental and peer influences on adolescent helping - Bartel, Jeffrey Scott (Kansas State University, 2006)
When adolescents are the subjects of developmental research into prosocial behaviors, the evidence suggests that both peers and parents are contributors to adolescents’ helping behavior. However, these two predictors are rarely studied concurrently. The present study explored the relative influence of parents and peers on (1) different types of adolescent helping (i.e., planned and spontaneous) and (2) different targets of spontaneous helping (i.e., friends, non-friends, and strangers) in 51 early (mean age = 12.54 years, 24 boys and 27 girls) and 57 middle (mean age = 16.82 years, 25 boys and 32 girls) adolescents. Adolescents and their parents completed parallel forms asking them to describe their planned helping as well as a questionnaire assessing past and anticipated future spontaneous helping of friends, strangers, and (for adolescents only) non-friends. Adolescents also reported their perception of their friendship group’s norm of helping as well as their level of identification with their friendship group. There was no clear age-related helping pattern, though a sex difference (females were generally more helpful than males) and an effect of target (friends were helped more than non-friends, who were in turn helped more than strangers) found in the adolescents was paralleled in the adults. Fathers’ planned helping was generally more strongly related to their adolescents’ planned helping than was mothers’ planned helping, though both mothers’ and fathers’ spontaneous helping of friends and family (though not of strangers) was strongly associated with their adolescents’ spontaneous helping. In contrast to parental variables’ relationship with both adolescent planned and spontaneous helping, peer variables were more consistently related to spontaneous than planned helping. Implications of the present findings, and proposed directions for future research, are discussed.
Keywords: parent; peer; adolescent; helping; prosocial; Psychology, Developmental (0620); Psychology, Social (0451)